2014
DOI: 10.1007/s12144-014-9264-z
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the Langner Symptom Survey for the College Population

Abstract: The sample consisted of 1,306 college students from four universities in the Midwestern United States. Participants' reported counseling status (never been in treatment or currently in treatment) was used to designate individuals as "well" or "ill" in calculating sensitivity and specificity. Results revealed that a Langner Symptom Survey (LSS) cutoff score of 5 was optimal regarding both sensitivity (0.76) and specificity (0.70) in identifying distressed individuals, rather than a score of 4, as established in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Of arguably greater importance and clinical significance is the finding that males of low spirituality tended to report symptoms at or above a clinically validated cutoff score denoting psychological distress and need for treatment (Handal et al 2015). Other research has suggested that a similar pattern between religion/spirituality and mental health exists, however the results have found that either no sex differences appear (Mosher and Handal 1997) or females, and not males, surpass the clinical cutoff score (Crawford et al 1989;Handal et al 1989).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Of arguably greater importance and clinical significance is the finding that males of low spirituality tended to report symptoms at or above a clinically validated cutoff score denoting psychological distress and need for treatment (Handal et al 2015). Other research has suggested that a similar pattern between religion/spirituality and mental health exists, however the results have found that either no sex differences appear (Mosher and Handal 1997) or females, and not males, surpass the clinical cutoff score (Crawford et al 1989;Handal et al 1989).…”
Section: Discussionmentioning
confidence: 91%
“…The moderate and high spirituality groups of males did not demonstrate significantly different LSS scores (p = 0.884). Notably, the mean LSS scores for males within in the low spirituality group (M = 5.30, SD = 4.46) fell above a clinically validated cutoff score of 5 (Handal et al 2015), thus denoting that males in the low spiritual group tended to report clinically significant psychological distress and need for treatment. These results are displayed in Table 3.…”
Section: Sts and Psychological Distressmentioning
confidence: 92%
See 2 more Smart Citations
“…Recent psychometric analysis of the LSS provided validity for a cutoff score of 5 denoting psychological distress and need for treatment in emerging adult populations (Handal et al 2015). In this study, college students currently in psychological treatment had a mean LSS score of 7.35 (SD = 2.75), which was significantly higher than students previously in treatment who reported a mean LSS score of 4.86 (SD = 3.60) and students who had never received psychological care reported a mean LSS score of 3.49 (SD = 3.98).…”
Section: Psychological Distressmentioning
confidence: 99%